2018
DOI: 10.17532/jhsci.2018.281
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of risk factors for hypertension in Dormaa municipality in Ghana using the World Health Organization STEPS approach

Abstract: Introduction: Hypertension (HPT) is a significant public health challenge worldwide and is the single most important risk factor for cardiovascular disease. As life expectancy rates improve in Ghana and the prevalence of risk factors increase, the burden of non-communicable diseases such as HPT is also expected to increase. However, little is known about the specific factors that predispose of Ghanaians to a higher risk of HPT. Methods: A cross-sectional study was conducted in the Dormaa Municipality in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…This could largely be due to the fact that majority did not belief in the current allopathic care for hypertension with more than half claiming not to trust the allopathic treatment for hypertension (Lee et al, 2013). This finding of low level of belief and trust in current allopathic care for hypertension is in line with those found by (Atibila et al, 2018; Cuffee et al, 2013; Nguyen et al, 2009) that reported low trust level in the biomedical model of care for chronic and non‐communicable diseases. This calls for structured approaches focusing more on community and individual engagement aimed at building trust in the biomedical approach to care so as to reduce the complications of diseases particularly NCDs which have assumed epidemic levels in Ghana (Atibila, Ten Hoor, et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This could largely be due to the fact that majority did not belief in the current allopathic care for hypertension with more than half claiming not to trust the allopathic treatment for hypertension (Lee et al, 2013). This finding of low level of belief and trust in current allopathic care for hypertension is in line with those found by (Atibila et al, 2018; Cuffee et al, 2013; Nguyen et al, 2009) that reported low trust level in the biomedical model of care for chronic and non‐communicable diseases. This calls for structured approaches focusing more on community and individual engagement aimed at building trust in the biomedical approach to care so as to reduce the complications of diseases particularly NCDs which have assumed epidemic levels in Ghana (Atibila, Ten Hoor, et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…The high level of adherence of males to treatment could be because of the male‐dominated decision‐making process in the Ghanaian society. Males are often the decision makers in the homes in Ghana whereas females and children need male consent to accept even treatment given to them in the hospital (Atibila et al, 2018; Lee et al, 2013). This study's finding on adherence is higher compared to the adherence level of 7% reported in Kumasi, Ghana (Bosu, 2015; Buabeng et al, 2004; Konlan, Armah‐mensah, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also implicated genetic predisposition, race, age, psychological stress, cultural beliefs, socio-economic, and environmental factors as essential risk factors for HPT [ 2 , 11 ]. Similarly, alcohol consumption, abdominal obesity, stress, and tobacco smoking have been identified as significant predictors for HPT in several countries [ 12 , 13 ], including Ghana [ 14 ]. Unlike in the past when HPT was linked to the elderly and the rich, recent studies have demonstrated high prominence of HPT among children and young adolescents as well [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…e prevalence of HPT in Ghana has gradually and progressively increased over the past two decades [7]. e current prevalence of HPT in Ghana is estimated to be between 30.1% and 40.0%, with an advance in age, excessive alcohol consumption, smoking, and physical inactivity considered as the major health risk factors [8][9][10]. Studies conducted in deprived areas in Accra reported a 28.3% prevalence of HPT.…”
Section: Introductionmentioning
confidence: 99%